Work-Family Conflict and Mindful Parenting: The Mediating Role of Parental Psychopathology Symptoms and Parenting Stress in a Sample of Portuguese Employed Parents - Moreira, Helena; Fonseca, Ana; Caiado, Brígida; Canavarro, Maria Cristina (Frontiers in Psychology, 2019)
Aims: The aims of the current study are to examine whether parents’ work-family conflict, emotional distress (anxiety/depressive symptoms and parenting stress) and mindful parenting vary according to the type of employment (full-time, part-time, and occasional), the type of work schedule (fixed, flexible and shift), and the number of working hours per week and to explore whether parental emotional distress mediates the association between work-family conflict and mindful parenting dimensions. Method: A sample of 335 employed parents (86.3% mothers) of children and adolescents between the ages of 1 and 19 years old completed a sociodemographic form and measures of work-family conflict, anxiety/depression symptoms, parenting stress, and mindful parenting. The differences in study variables among types of employment, work schedules and number of weekly working hours were analyzed. A path model was tested through structural equation modeling in AMOS to explore the indirect effect of work-family conflict on mindful parenting dimensions through anxiety, depression and parenting stress. The invariance of the path model across children’s age groups (toddlers, preschool and grade school children, and adolescents) and parents’ gender was also examined. Results: Parents with a shift work schedule, working full-time and 40 hours or more per week, presented significantly higher levels of work-family conflict than those with a fixed or flexible schedule, working part-time and less than 40 hours per week, respectively. Parents with a flexible work schedule presented significantly higher levels of self-regulation in parenting and of nonjudgmental acceptance of parental functioning than parents with a shift work schedule. Higher levels of work-family conflict were associated with lower levels of mindful parenting dimensions through higher levels of anxiety/depression symptoms and parenting stress. The model was invariant across children’s age groups and parents’ gender. Discussion: Work-family conflict is associated with poorer parental mental health and with less mindful parenting. Workplaces should implement family-friendly policies (e.g., flexible work arrangements) that help parents successfully balance the competing responsibilities and demands of their work and family roles. These policies could have a critical impact on the mental health of parents and, consequently, on their parental practices.